Proton Skins, Neutron Skins, and Proton Radii of Mirror Nuclei - Sammarruca, Francesca (Frontiers in Physics, 2018)
We present predictions for proton skins based on isospin-asymmetric equations of state derived microscopically from high-precision chiral few-nucleon interactions. Moreover, we investigate the relation between the neutron skin of a nucleus and the difference between the proton radii of the corresponding mirror nuclei.